115k views
0 votes
F(x)=−5x^3−4x^2+8x and g(x)=−4x^2+8, find (f−g)(x) and (f−g)(−2).

User Eli Dagan
by
5.4k points

1 Answer

4 votes

Answer:

see explanation

Explanation:

(f - g)(x) = f(x) - g(x) , that is

f(x) - g(x)

= - 5x³ - 4x² + 8x - (- 4x² + 8) ← distribute parenthesis by - 1

= - 5x³ - 4x² + 8x + 4x² - 8 ← collect like terms

= - 5x³ + 8x - 8

Substitute x = - 2 into this expression, thus

(f - g)(- 2)

= - 5(- 2)³ + 8(- 2) - 8

= - 5(- 8) - 16 - 8

= 40 - 16 - 8

= 16

User Chris Ammerman
by
5.4k points